2016
DOI: 10.1016/j.lungcan.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance Practice Patterns after Curative Intent Therapy for Stage I Non-Small-Cell Lung Cancer in the Medicare Population

Abstract: Objectives Recurrence after treatment for non-small cell lung cancer (NSCLC) is common, and routine imaging surveillance is recommended by evidence-based guidelines. Little is known about surveillance patterns after curative intent therapy for early stage NSCLC. We sought to understand recent practice patterns for surveillance of stage I NSCLC in the first two years after curative intent therapy in the Medicare population. Materials and Methods Using the Surveillance, Epidemiology, and End Results (SEER)-Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…Variability of surveillance in clinical practice is even greater, with adherence to guidelines often being quite poor. In a study of adherence to NCCN and ACCP guidelines, Erb et al utilized the Surveillance, Epidemiology, and End Results (SEER)-Medicare database and found that only 61.4% of stage I NSCLC patients received guideline-adherent surveillance during the initial 2 years after treatment 14 . Poor adherence can be partially explained by the paucity of quality longitudinal data to inform best practice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability of surveillance in clinical practice is even greater, with adherence to guidelines often being quite poor. In a study of adherence to NCCN and ACCP guidelines, Erb et al utilized the Surveillance, Epidemiology, and End Results (SEER)-Medicare database and found that only 61.4% of stage I NSCLC patients received guideline-adherent surveillance during the initial 2 years after treatment 14 . Poor adherence can be partially explained by the paucity of quality longitudinal data to inform best practice.…”
Section: Resultsmentioning
confidence: 99%
“…In the real world, patients and physicians often deviate from interval-based regimens (especially as time from primary treatment increases). Previous studies have documented remarkably low adherence to existing guideline-recommended surveillance regimens, approximating 60% 14 . Additionally, one must contend with several biases when quantifying surveillance in observational research.…”
Section: Resultsmentioning
confidence: 99%
“…28 Although not recommended in routine follow-up after SBRT, 18 F-FDG PET/CT is frequently performed alternately with CT. For example, a recent study found that less than two-thirds of patients had this monitoring in line with recommendations. 30 Given that no SUV max has exceeded the threshold of 5 in case of RP in this study, it is conceivable to propose a PET/CT scan in cases of doubt between tumour recurrence and RP on CT scan, which remains the reference for follow-up.…”
mentioning
confidence: 79%
“…Thus, the combination of EMAF and clinical information could significantly improve the predictive performance for 3-year overall survival. Early-stage lung cancer patients are expected to have favorable clinical prognosis, although they actually have diverse survival outcomes ( 33 ), which may be due to timing for treatment after surgery ( 34 ). EMAF appears to identify a subset of early-stage patients with relatively poor prognosis, which may indicate an alternative preoperative chemotherapy or radiation strategy followed by surgery.…”
Section: Discussionmentioning
confidence: 99%